Methylene blue and metformin photocatalytic activity of CeO2-Nb2O5 coatings is dependent on the treatment time of plasma electrolytic oxidation on titanium - Orsetti, Fábio R. [UNESP]; Bukman, Laís [UNESP]; Santos, Janaina S.; Nagay, Bruna E.; Rangel, Elidiane C. [UNESP]; Cruz, Nilson C. [UNESP] (Elsevier, 2021)
Despite UV photolysis is common industrial water treatment, existent approaches are still not fully effective nor practical due to the growing amount of discharged effluents. Titanium dioxide (TiO2) has been used as a semiconductor for photocatalytic degradation of pollutants, but its efficiency is limited due to its rapid reverse reaction. Thus, novel approaches are needed to improve the quality and cost benefits of photocatalysts. In this study, the processing time effect of CeO2-Nb2O5 coatings on titanium synthesized via a one-step method of Plasma Electrolytic Oxidation (PEO) in an electrolytic solution containing ammonium niobium oxalate salt [NH4NbO(C2O4)2] and cerium oxide (CeO2) powder at 300, 450, and 600 s. The structural and optical properties, morphology, wettability, coating thickness, and elemental chemical composition were investigated. The performance of CeO2-Nb2O5 coatings regarding the photocatalytic activity was evaluated under UV irradiation, using methylene blue (MB) and metformin as model pollutants. Energy Dispersive Spectroscopy confirmed the incorporation of Ce and Nb into the oxide film. The Scanning Electron Microscopy demonstrated that the PEO process produced CeO2-Nb2O5 coatings with a thickness from 9.6 to 55.8 µm and irregular and porous structures that changed in proportion and size according to treatment time. X-ray diffraction (XRD) analysis revealed that the coatings demonstrated crystallization corresponding to CeO2 and Nb2O5 phases. All the experimental groups presented an estimated band gap of 3.3 eV, suggesting that the obtained coatings could be active in the UV light range. Also, such coatings showed an increased surface area that varied from 3.93 to 5.62 cm2 as high it was the treatment time, which could facilitate the degradation of pollutants. These results were consistent with the photocatalytic activity assay, where samples treated for 600 s showed the most significant degradation of MB under UV irradiation, especially at 15 and 30 min of irradiation when compared to untreated titanium and photolysis process (p < 0.05). Regarding metformin, after 120 min of UV exposure, 27% was degraded due to photolysis. Whereas after 210 min, 67% of the pharmaceutical degradation was observed on the 600 s-treated CeO2-Nb2O5 coating. A crystalline CeO2-Nb2O5 coating with improved surface characteristics and photocatalytic activity was synthesized by tailoring the treatment time process. This study makes advantageous for degrading pollutants and medicines, since sewage treatment systems are sometimes slow or not fully effective.
Keywords: CeO2; Heterogeneous photocatalysis; Metformin; Methylene blue dye; Nb2O5; Plasma electrolytic oxidation